Species and functional plant diversity enhance ecosystem functions in the central Monte desert - Chaves, Jimena Elizabeth (2020)
Questions: Niche complementarity has been proposed as the underlying mechanism for optimizing resource use of plants in diverse ecosystems, usually associated with their functional traits and not with the species number per se. Our main questions were: (a) does species diversity optimize the use of resources in arid ecosystems; (b) is there redundancy of species in the use of water and nutrients; and (c) what diversity components most affect ecosystem functions of water regulation and material cycling?. Location: Central Monte desert, Argentina. Methods: We selected vegetation patches with different species (SD) and functional diversities (FD), where we measured indicators of water regulation and material cycling. At two soil depths, we measured soil nitrate, phosphate, organic matter, chloride, electrical conductivity, and pH. We also determined decomposition, plant water use efficiency (foliar δ13C of C3 plants), and nitrogen use (δ15N). These variables were used as response variables, while total plant cover, species richness, Shannon, Simpson, evenness, and Rao's functional diversity indexes were used as predictors. Results: At the soil surface, response variables were better explained by models that included diversity (SD, FD or both) instead of evenness, total plant cover or null model. A diversity effect was not detected in deeper soil layers for most variables, except for electric conductivity, which had a positive effect on FD. Richness explained plant δ13C but had no influence on plant δ15N. Conclusions: Diversity of plant community influences ecosystem processes, as it increases decomposition, soil organic matter, and nutrient availability at the surface, and decreases water losses to the subsoil and plant water use efficiency. Both SD and FD explained one or more ecosystem processes of water regulation and material cycling, suggesting that individual species contribute to ecosystem functioning, with a low redundancy for arid areas.